2022
DOI: 10.1177/10732748221133987
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Diet and Physical Activity Intervention for Hispanic/Latina Breast Cancer Survivors

Abstract: Objectives There is limited guidance on how to effectively educate cancer survivors to adopt and maintain specific diet and physical activity recommendations, especially among underserved and under-resourced populations. Here, the objective is to present the development of a behavioral and theoretically-based multi-modal diet and physical activity intervention program for Hispanic/Latina breast cancer survivors, Mi Vida Saludable (My Healthy Life). Methods The development process was based on the 6 steps of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(35 citation statements)
references
References 67 publications
(131 reference statements)
0
35
0
Order By: Relevance
“…Key factors for program effectiveness include social support, patient motivation, and meticulous planning [ 87 ]. The utilization of the DESIGN procedure has shown efficacy in constructing similar programs [ 88 ]. However, evidence for the long-term maintenance of physical activity post-exercise intervention for individuals living with or beyond cancer is limited and inconclusive, emphasizing the need for follow-ups to assess intervention efficacy [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Key factors for program effectiveness include social support, patient motivation, and meticulous planning [ 87 ]. The utilization of the DESIGN procedure has shown efficacy in constructing similar programs [ 88 ]. However, evidence for the long-term maintenance of physical activity post-exercise intervention for individuals living with or beyond cancer is limited and inconclusive, emphasizing the need for follow-ups to assess intervention efficacy [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 shows the number of studies across the continuum, including preclinical, clinical, and translation and implementation trials. Two studies were determined to be efficacy trials (Women's Healthy Eating and Living or WHEL study) [51,52] and Mi Vida Saludable [44][45][46]), based on having a previous feasibility or pilot study published (WHEL pilot [53] and Cocinar para Su Salud [38][39][40]). The WHEL pilot was not considered for this review [53], because no data were reported on race or ethnicity, likely due to the timing of the study in the 1990s, but this review included Cocinar para Su Salud [38][39][40], the pilot study for Mi Vida Saludable [44][45][46].…”
Section: Methodsmentioning
confidence: 99%
“…Two studies were determined to be efficacy trials (Women's Healthy Eating and Living or WHEL study) [51,52] and Mi Vida Saludable [44][45][46]), based on having a previous feasibility or pilot study published (WHEL pilot [53] and Cocinar para Su Salud [38][39][40]). The WHEL pilot was not considered for this review [53], because no data were reported on race or ethnicity, likely due to the timing of the study in the 1990s, but this review included Cocinar para Su Salud [38][39][40], the pilot study for Mi Vida Saludable [44][45][46]. in this scoping review (Table 1): Avanzando Juntas [36], Bronx Oncology Living Daily (BOLD) Healthy Living [37], Cocinar para Su Salud [38][39][40], La Vida Activa [41], LIVES (Lifestyle Intervention for Ovarian Cancer Enhanced Survival) [42,43], Mi Vida Saludable [44][45][46], My Health [47], Nuestra Salud [48], Prescription (Rx) for Better Breast Health [49,50], and WHEL (Women's Healthy Eating and Living Study) [51,52].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations